POTENSI TEGAKAN PADA KAWASAN CAGAR ALAM LO FAT PUN FIE KECAMATAN MONTERADO KABUPATEN BENGKAYANG - Dewantara, Iswan; manurung, kartika chandra; Widhanarto, Ganjar Oki (JURNAL HUTAN LESTARI, 2023)
The Lo Fat Pun Fie Nature Reserve with an area of 7.8 Ha has Batik Orchids (Vanda hokeriana) and Pitchers (Nepenthes spp) as characteristics of this nature reserve that need to be preserved. The existence of orchids and pitcher plants is closely related to the existence of the types of vegetation that make up the Lo Fat Fun Pie Nature Reserve. This research aims to record tree species and analyze the potential for stands in the area. This research was carried out using the Systematics Strip Sampling with Random Start method with a sampling intensity of 15%, observations in the research area using 4 paths with varying lengths, where the first path was determined randomly and then continued with a distance between paths of 133 meters, with a total of 29 observation measuring plots. . Based on the results of data analysis, it was found that the average stand potential in the Lo Pat Fun Pie Nature Reserve per hectare was 286 stems 96.60 m3 with a minimum potential range of 1,162.40 stems 746.05 m3 and a maximum of 3,264.05 stems 748.99 m3.Keywords: forest inventory, nature reserves, stand potential.AbstrakCagar Alam Lo Fat Pun Fie dengan Luas 7,8 Ha memiliki Anggrek Batik (Vanda hokeriana) dan Kantong Semar (Nepenthes spp) sebagai ciri khas cagar alam ini yang perlu dilestarikan. Keberadaan jenis anggrek dan kantong semar sangat erat kaitan dengan keberadaan jenis-jenis vegetasi penyusun Cagar Alam Lo Fat Fun Pie Tujuan penelitian ini untuk mendata jenis pohon dan menganalisa potensi tegakan pada kawasan. Penelitian ini dilakukan dengan metode Systematics Strip Sampling with Random Start dengan intensitas sampling 15%, pengamatan pada kawasan penelitian menggunakan 4 jalur dengan panjang bervariasi, dimana penetuan jalur pertama secara random kemudian dilanjutkan secara dengan jarak antar jalur 133 meter, dengan total 29 petak ukur pengamatan. Berdasarkan hasil analisis data, didapatkan potensi tegakan di Cagar Alam Lo Pat Fun Pie rata-rata per hektar 286 batang 96,60 m3 dengan rentang potensi minimum 1.162,40 batang 746,05 m3 dan maksimum 3.264,05 batang 748,99 m3.Kata kunci: inventarisasi hutan, cagar alam, potensi tegakan.